Air Blowing Oxidation Process for Improving of Rheological Properties of Sulfur Treated Asphalt - Wijdan Saleh (College of Education for Pure Sciences, 2020)
There is a growing need for the production of a certain types of asphaltic materials having a good rheological properties compared with the non-modified a asphaltic materials can be using as a paving materials. In this research Rheological properties of Beije asphalt modified using oxidation process in the present of Sulphur and chlorides of (iron and zink). In this research we obtained asphaltic materials which can be used in paving and mastic according to the measuring of the (ductility, penetration and softening point.